Libertarny radykalizm - Juruś, Dariusz (Uniwersytet im. A. Mickiewicza w Poznaniu Wydział Nauk Społecznych, Instytut Filozofii UAM, 2014)
In the paper I identify foundations of radical libertarianism, which could be called libertarianism in a sensu stricto. This sense is perceived from the Rothbardian’s perspective, whose theory of property is pivotal for our considerations. Murray N. Rothbard claims that property rights, which are derived from the principle of self-possession, are absolute. The absoluteness of property rights is the core of our standpoint. We argue that to define libertarianism in a strict sense we need also, as supportive elements: (i) the doctrine of natural rights, on the ethical level; (ii) the Austrian theory of economy, on the level of economics; and (iii) individualistic anarchism, on a political level. We believe that the absolute right to property and these three theories can be considered as a coherent theory which we can call libertarianism in a strict sense.
Radical libertarianism
Keywords: libertarianism; property; self-possession; non-agression; Austrian School of Economics; natural law doctrine; individualistic anarchism